Self‐Healing and Light‐Soaking in MAPbI3: The Effect of H2O. Issue 35 (29th July 2022) - Ceratti, Davide Raffaele; Tenne, Ron; Bartezzaghi, Andrea; Cremonesi, Llorenç; Segev, Lior; Kalchenko, Vyacheslav; Oron, Dan; Potenza, Marco Alberto Carlo; Hodes, Gary; Cahen, David
Abstract: The future of halide perovskites (HaPs) is beclouded by limited understanding of their long‐term stability. While HaPs can be altered by radiation that induces multiple processes, they can also return to their original state by "self‐healing." Here two‐photon (2P) absorption is used to effect light‐induced modifications within MAPbI3 single crystals. Then the changes in the photodamaged region are followed by measuring the photoluminescence, from 2P absorption with 2.5 orders of magnitude lower intensity than that used for photodamaging the MAPbI3 . After photodamage, two brightening and one darkening process are found, all of which recover but on different timescales. The first two are attributed to trap‐filling (the fastest) and to proton‐amine‐related chemistry (the slowest), while photodamage is attributed to the lead‐iodide sublattice. Surprisingly, while after 2P‐irradiation of crystals that are stored in dry, inert ambient, photobrightening (or "light‐soaking") occurs, mostly photodarkening is seen after photodamage in humid ambient, showing an important connection between the self‐healing of a HaP and the presence of H2 O, for long‐term steady‐state illumination, practically no difference remains between samples kept in dry or humid environments. This result suggests that photobrightening requires a chemical‐reservoir that is sensitive to the presence of H2 O, or possibly other proton‐related, particularly amine, chemistry. Abstract : The two‐photon‐induced photodamage and consequent self‐healing inside MAPbI3 single crystals are investigated. Two photobrightening and one photodarkening process are identified, which are connected to trap‐filling, methylamine‐chemistry, and the lead‐halide sublattice. H2 O is found to strongly influence the overall photodamage and kinetics of the self‐healing process, showing an important connection between self‐healing and the presence of H2 O.